Effects of Soil Temperature and Moisture on the Development and Survival of Grasshopper Eggs in Inner Mongolian Grasslands - Wu, Tingjuan; Hao, Shuguang; Kang, Le (Frontiers in Ecology and Evolution, 2021)
Grasshopper eggs overwinter in soil for almost half a year; changes in soil temperature and moisture have a substantial effect on grasshopper eggs, especially temperature and moisture extremes. However, the combinatorial effect of temperature and moisture on the development and survival of grasshopper eggs has not been well studied. Here, we examined the effects of different soil moistures (2%, 5%, 8%, 11%, 14% water content) at 26°C and combinations of extreme soil moisture and soil temperature on the egg development and survival of three dominant species of grasshopper (Dasyhippus barbipes, Oedaleus asiaticus, and Chorthippus fallax) in Inner Mongolian grasslands. The egg water content of the three grasshopper species was positively correlated with soil moisture but negatively correlated with hatching time. The relationship between hatching rate and soil moisture was unimodal. Averaged across 2% and 11% soil moisture, a soil temperature of 35oC significantly advanced the egg hatching time of D. barbipes, O. asiaticus, and C. fallax by 5.63, 4.75 and 2.63 days and reduced the egg hatching rate of D. barbipes by 18%. Averaged across 26 and 35°C, 2% soil moisture significantly delayed the egg hatching time of D. barbipes, O. asiaticus, and C. fallax by 0.69, 11.01 and 0.31 days, respectively, and decreased the egg hatching rate of D. barbipes by 10%. The hatching time was prolonged as drought exposure duration increased, and the egg hatching rate was negatively correlated with drought exposure duration, except for O. asiaticus. Overall, the combination of high soil temperature and low soil moisture had a significant negative effect on egg development, survival, and egg hatching. Generally, the response of grasshopper eggs to soil temperature and moisture provides important information on the population dynamics of grasshoppers and their ability to respond to future climate change.